2016
DOI: 10.1242/jeb.148700
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium uptake during hypoxia in developing zebrafish, Danio rerio, is mediated by hypoxia-inducible factor

Abstract: The present study investigated the potential role of hypoxia-inducible factor (HIF) in calcium homeostasis in developing zebrafish (Danio rerio). It was demonstrated that zebrafish raised in hypoxic water (30 mmHg; control, 155 mmHg P O2 ) until 4 days post-fertilization exhibited a substantial reduction in whole-body Ca 2+ levels and Ca 2+ uptake. Ca 2+ uptake in hypoxia-treated fish did not return to prehypoxia (control) levels within 2 h of transfer back to normoxic water. Results from real-time PCR showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Morpholino experiments and analysis of Hif-1αB-deficient zebrafish embryos confirmed that ECAC expression was under the control of Hif-1αB ( Fig. 4), which was not the case for expression of the plasma membrane Ca 2+ -ATPase (PMCA) and the sodium-dependent Ca 2+ transporter (NXC1b) (Kwong et al, 2016).…”
Section: The Role Of Hif Proteins In Ionic Regulationmentioning
confidence: 92%
See 1 more Smart Citation
“…Morpholino experiments and analysis of Hif-1αB-deficient zebrafish embryos confirmed that ECAC expression was under the control of Hif-1αB ( Fig. 4), which was not the case for expression of the plasma membrane Ca 2+ -ATPase (PMCA) and the sodium-dependent Ca 2+ transporter (NXC1b) (Kwong et al, 2016).…”
Section: The Role Of Hif Proteins In Ionic Regulationmentioning
confidence: 92%
“…In addition to Na + and Cl − , freshwater fish also take up Ca 2+ from the environmental water. Hypoxia impairs Ca 2+ uptake in developing zebrafish embryos, and Ca 2+ uptake has been shown to remain low even after reoxygenation (Kwong et al, 2016). The decrease in Ca 2+ uptake was shown to be caused by a decrease in the expression level of an epithelial Ca 2+ channel (ECAC).…”
Section: The Role Of Hif Proteins In Ionic Regulationmentioning
confidence: 99%
“…Hypoxia inhibited Ca 2+ uptake in zebrafish, Danio rerio (KWONG et al, 2016), and consequently the exposure of silver catfish to high Ca 2+ levels may facilitate the maintenance of plasma Ca 2+ levels and partially reduce the effect of tissue hypoxia (higher muscle lactate levels) provoked by high NO 2 -levels. The high Ca 2+ level alone was sufficient to reduce hepatic carbohydrate and protein levels of silver catfish in the present study.…”
Section: Coltmentioning
confidence: 99%